High-resolution small RNA structures from exact nuclear Overhauser enhancement measurements without additional restraints - Nichols, Parker J.; Henen, Morkos A.; Born, Alexandra; Strotz, Dean; Güntert, Peter; Vögeli, Beat (Communications biology, 2018)
RNA not only translates the genetic code into proteins, but also carries out important cellular functions. Understanding such functions requires knowledge of the structure and dynamics at atomic resolution. Almost half of the published RNA structures have been solved by nuclear magnetic resonance (NMR). However, as a result of severe resonance overlap and low proton density, high-resolution RNA structures are rarely obtained from nuclear Overhauser enhancement (NOE) data alone. Instead, additional semi-empirical restraints and labor-intensive techniques are required for structural averages, while there are only a few experimentally derived ensembles representing dynamics. Here we show that our exact NOE (eNOE) based structure determination protocol is able to define a 14-mer UUCG tetraloop structure at high resolution without other restraints. Additionally, we use eNOEs to calculate a two-state structure, which samples its conformational space. The protocol may open an avenue to obtain high-resolution structures of small RNA of unprecedented accuracy with moderate experimental efforts. Parker Nichols et al. present an exact nuclear Overhauser enhancement (eNOE) protocol for defining small RNA structures at high resolution using only NOE distance data. They apply eNOE to a 14-mer UUCG tetraloop structure, obtaining a decrease in root-mean-square deviation from 1.52 Å to 0.44 Å, compared to conventional NOE.